The role of internal control and audit in improving the performance of government institutions: A case study of the Iraqi housing fund - Farhan, Raghad M. (Edelweiss Applied Science and Technology, 2024)
This study aimed to assess the impact of internal control and auditing on government institution performance, using Iraq’s Housing Fund as a case study. The study population comprised all Iraqi Housing Fund branches, with a sample of 114 respondents from financial managers, accounting heads, internal audit managers, and accounting/audit staff. Findings confirmed that internal control and auditing significantly influence government institution performance, as exemplified by the Iraqi Housing Fund. Based on these results, the study recommends the Housing Fund maintain its commitment to internal control and auditing due to their performance-enhancing role. Additionally, it suggests enhancing auditors’ professional competence through training to align with industry advancements.